2005
DOI: 10.1111/j.1442-2042.2005.01071.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of penoscrotal abnormalities and inguinal hernia in elementary‐school boys in the west of Iran

Abstract: Aim : We designed a cross-sectional study in order to determine the prevalence of inguinal hernia and penoscrotal abnormalities in the Lorestan province, situated in the west of Iran. Methods : We studied 3205 elementary-school boys, aged 6-12 years, who underwent clinical examinations of the groin and genitalia in 2002.Results : Abnormalities were detected in 213 children (6.64%). The most frequent anomaly was indirect inguinal hernia, seen in 78 children (2.4%). The other abnormalities were retractile testes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 18 publications
0
13
2
1
Order By: Relevance
“…We also found a significantly increased prevalence of inguinal hernias (43%), and hydroceles (36%) in affected men when compared with unaffected male relatives (0%), and a statistically significant greater prevalence of hernias in affected men with TCF8 mutations (100%) compared with affected men without TCF8 mutations (20%). As the estimated prevalence of inguinal hernias in male newborns and boys is estimated to be between 1% and 2.4% [Choi et al, 1989; Yucesan et al, 1993; Kapur et al, 1998; Chandrakala and Vijayashankara, 2005; Yegane et al, 2005] the prevalence rates observed in men affected with PPCD, both with and without TCF8 mutations, are significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…We also found a significantly increased prevalence of inguinal hernias (43%), and hydroceles (36%) in affected men when compared with unaffected male relatives (0%), and a statistically significant greater prevalence of hernias in affected men with TCF8 mutations (100%) compared with affected men without TCF8 mutations (20%). As the estimated prevalence of inguinal hernias in male newborns and boys is estimated to be between 1% and 2.4% [Choi et al, 1989; Yucesan et al, 1993; Kapur et al, 1998; Chandrakala and Vijayashankara, 2005; Yegane et al, 2005] the prevalence rates observed in men affected with PPCD, both with and without TCF8 mutations, are significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…The interesting thing was that 60.1% of the parents were not conscious of their male children's abnormalities. [14]…”
Section: Discussionmentioning
confidence: 99%
“…Hidrosel için elde edilen sonuçlar Akay ve ark., [14] Şahin ve ark., [18] Remzi ve ark. [23] çalışmalarında sırasıyla %0.4, %1.2 %0.7 ve %0.9 olarak tespit edilmiştir. [23] çalışmalarında sırasıyla %0.4, %1.2 %0.7 ve %0.9 olarak tespit edilmiştir.…”
Section: Discussionunclassified